Avian schistosomes and outbreaks of cercarial dermatitis - Horák, Petr; Mikeš, Libor; Lichtenbergová, Lucie; Skála, Vladimír; Soldánová, Miroslava; Brant, Sara Vanessa (Clinical microbiology reviews, 2015)
Cercarial dermatitis (swimmer's itch) is a condition caused by infective larvae (cercariae) of a species-rich group of mammalian and avian schistosomes. Over the last decade, it has been reported in areas that previously had few or no cases of dermatitis and is thus considered an emerging disease. It is obvious that avian schistosomes are responsible for the majority of reported dermatitis outbreaks around the world, and thus they are the primary focus of this review. Although they infect humans, they do not mature and usually die in the skin. Experimental infections of avian schistosomes in mice show that in previously exposed hosts, there is a strong skin immune reaction that kills the schistosome. However, penetration of larvae into naive mice can result in temporary migration from the skin. This is of particular interest because the worms are able to migrate to different organs, for example, the lungs in the case of visceral schistosomes and the central nervous system in the case of nasal schistosomes. The risk of such migration and accompanying disorders needs to be clarified for humans and animals of interest (e.g., dogs). Herein we compiled the most comprehensive review of the diversity, immunology, and epidemiology of avian schistosomes causing cercarial dermatitis.
Keywords: Animals; Host Specificity; Schistosomiasis; Bird Diseases; biodiverzita; epidemický výskyt choroby; lidé; Biodiversity; zvířata; nemoci ptáků; Disease Outbreaks; parazitární onemocnění kůže; Skin Diseases, Parasitic; hostitelská specificita; schistosomóza; Humans